Communication Partners Supporting Children With Complex Communication Needs Who Use AAC: A Systematic Review. (November 2015) - Shire, Stephanie Y.; Jones, Nancy
Communication partners who efficiently use augmentative and alternative communication (AAC) are essential interaction partners for children learning to communicate using AAC. This systematic review examines studies targeting interventions designed to help communication partners support children with complex communication needs who use AAC. Overall, the 13 studies of moderate methodological quality rated using published rating scales reported positive findings for partners' skills and children's communication. Author-reported effect sizes and calculation of improvement rate difference indicated that multiple studies demonstrated large effects that were maintained 1 to 2 months post intervention. Delivery considerations for partner training including device training, enhancing partners' understanding of communication targets, and the timing of partner training are discussed. The importance of supporting successful interactions across learning contexts and domains of communication as well as over time is highlighted. Furthermore, implications for dyads with unique characteristics including limited experience with AAC and children who are developmentally young are examined.